Tracking methicillin-resistant Staphylococcus aureus clones in Colombian hospitals over 7 years (1996-2003): emergence of a new dominant clone (2005)
Worldwide dissemination of methicillin-resistant Staphylococcus aureus (MRSA) clones is a well-characterised phenomenon. Two hundred isolates of MRSA recovered from 17 Colombian hospitals collected between 2001 and 2003 were characterised by pulsed-field gel electrophoresis (PFGE). A new dominant electrophoretic pattern unrelated to previously characterised clones in Colombia was detected in 137 (68.5%) of these isolates. Only 40 (20%) isolates still showed a pattern closely related to a previously described dominant clone. The new electrophoretic pattern was indistinguishable from a cluster of isolates recovered in Chile between 1996 and 1998. Isolates from this clonal cluster exhibited multidrug resistance but were susceptible to linezolid and glycopeptides. The results indicate a shift in the population genetics of Colombian MRSA and confirm dissemination of the Chilean clone for the first time.